2017
DOI: 10.1017/s204017441700068x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological morbidity and parenting stress in mothers of primary school children by timing of acquisition of HIV infection: a longitudinal cohort study in rural South Africa

Abstract: Longitudinal maternal mental health data are needed from high HIV prevalence settings. The Siyakhula Cohort (SC) is a population-based cohort of HIV-positive and negative mothers (n=1506) with HIV-negative children (n=1536) from rural South Africa. SC includes 767 HIV-negative mothers; 465 HIV-positive in pregnancy; 272 HIV-positive since pregnancy (n=2 missing HIV status). A subgroup (n=890) participated in a non-randomized breastfeeding intervention [Vertical Transmission Study (VTS)]; the remaining (n=616) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Importantly, parenting stress scores were normally distributed. The measures used in this study have been widely used in this population [21,22,26,27] and showed good reliability in this study (Cronbach alpha: AUDIT α=0.92, PHQ-9 α=0.81, GAD-7 α=0.81, PSI-36 α=0.89).…”
Section: Methodsmentioning
confidence: 67%
See 2 more Smart Citations
“…Importantly, parenting stress scores were normally distributed. The measures used in this study have been widely used in this population [21,22,26,27] and showed good reliability in this study (Cronbach alpha: AUDIT α=0.92, PHQ-9 α=0.81, GAD-7 α=0.81, PSI-36 α=0.89).…”
Section: Methodsmentioning
confidence: 67%
“…[19,21] Cognitive, mental health and parenting data were collected on their biological mother or primary caregiver. [22] The HIV status of all enrolled women and children was known, and testing was offered to those who were unsure of their current status. We excluded children who were HIV-positive, as this cohort was established to examine developmental outcomes and associations with early-life factors, and these children have HIV-specific developmental risks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV-infected mothers face particular mental health risks, which in in turn impact their children’s mental health, and population-based data from pregnancy and across the life course is needed in African settings is to improve prevention and treatment. Rochat et al 8 . report the prevalence of psychological morbidity and factors associated with it in mothers during pregnancy in rural South Africa in their paper ‘Psychological morbidity and parenting stress in mothers of primary school children by timing of acquisition of HIV infection: a longitudinal cohort study in rural South Africa’; those HIV positive and HIV negative were compared.…”
mentioning
confidence: 99%